PENERAPAN ALGORITMA WEIGHTED TREE SIMILARITY UNTUK PENCARIAN SEMANTIK - Riyanarto Sarno; Faisal Rahutomo (JUTI: Jurnal Ilmiah Teknologi Informasi, 2008)
Full-text search and metadata-enabled search have weakness in the precision of the searched article. This research offers weighted tree similarity algorithm combined with cosine similarity method to count similarity in semantic search. In this method metadata is constructed based on the tree of labelled node, labelled and weighted branch. The structure of tree metadata is constructed based on semantic information like taxonomi, ontologi, preference, synonim, homonym and stemming. From testing result, the precision of search using weighted tree similarity algorithm is better that full-text search and metadata-enabled search.